Perspectives on Arabic Linguistics : Papers from the Annual Symposium on Arabic Linguistics. Volume V: Ann Arbor, Michigan 1991. - Eid, Mushira (John Benjamins Pub. Co., 1993)
The papers in the first section of this volume, 'Variation in Arabic', deal with a wide range of topics: the function of Modern Standard Arabic (MSA) vs. dialect variation in political speeches, patterns of variation in concord in Cairene dialect, the extent to which Cairenes 'know' MSA, and the scope of emphaticization in different dialects. In the section on 'Phonological Perspectives' there are papers dealing with emphasis spread and with gemination/degemination/antigemination in Iraqi Arabic. The papers in the section on syntax, all focused on MSA and within a GB framework, discuss aspects o.